2021
DOI: 10.1007/s00170-021-07448-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MQL performances using various nanofluids in turning of AISI 304 stainless steel

Abstract: In recent years, the need for eco-friendly machining processes has increased dramatically in order to limit the excessive use of conventional cutting fluids, thereby reducing their negative effects on both environment and operator's health. In this context, dry cutting, minimum quantity lubrication (MQL) and nanofluid assisted MQL, as environmentally alternatives, have been positively shown their significance to overcome this problem. This experimental study was conducted from the perspective of performance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 46 publications
0
9
0
1
Order By: Relevance
“…( 3) and (4) as characteristic equations, the upper and lower limits of the solution set are shown in Table 6, the properties of each operator correspond to Table 7, and the limit equation adopts Eq. (10).…”
Section: Optimization Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…( 3) and (4) as characteristic equations, the upper and lower limits of the solution set are shown in Table 6, the properties of each operator correspond to Table 7, and the limit equation adopts Eq. (10).…”
Section: Optimization Resultsmentioning
confidence: 99%
“…They concluded that the surface roughness observed with minimum quantity lubrication turning was lower than dry turning [9]. Touggui et al [10] conducted a study to improve the machining performance in turning on AISI 304 austenitic stainless steel (ASS) under dry, minimum quantity lubrication, nanofluids, and hybrid nanofluid-assisted minimum quantity lubrication conditions. The main purpose of this experimental study is to evaluate and compare the effect of dispersed nano-additives in the vegetable cutting fluid on the responses under consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Touggui ve diğ. MoS2, MWCNT, grafen, MWCNT/MoS2 ve grafen/MoS2 katkı maddelerini ekledikleri nanoakışkanları saf MMY ve kuru işlemeyle kıyaslamışlardır [11]. Deney sonuçlarını analiz eden araştırmacılar nanoakışkanların bariz bir şekilde iyileştirme sunduğunu rapor etmişlerdir.…”
Section: öZetunclassified
“…For these reasons, the dry machining method without using cutting fluid is becoming more and more popular. Even if the negative effects of cutting fluids are eliminated in dry machining, it is very difficult to abandon the use of cutting fluids due to high efficiency and performance advantages in machining [4], [5]. In dry machining, there is relatively more friction and adhesion and higher temperatures at the cutting tool and workpiece interface [6].…”
Section: Introduction (Gi̇ri̇ş)mentioning
confidence: 99%